Radiation modification of Ni nanotubes by electrons; Materials Research Express; Vol. 4, iss. 10 - Kozlovskiy A. L. Artem Leonidovich; Kaykanov M. I. Marat Islambekovich; Tikhonov A. V. Aleksandr Vladimirovich; Kenzhina I. Е. Inesh; Ponomarev D. V. Denis Vladimirovich; Zdorovets M. V. Mikhail Viktorovich (2017, 2017)
Title screen